Caracterização das inter-relações entre geologia e geomorfologia a partir do sensoriamento remoto e geoprocessamento na bacia hidrográfica do rio Japaratuba, Sergipe - Brasil - Lima, Sanmy Silveira (2017)
The techniques of image and data processing allowed to characterize and analyze the geological-geomorphological interrelationships of the Japaratuba River Basin, located in the state of Sergipe - Brazil. To obtain the results, based on the methodology, filtering techniques were applied in orbital data highlighting the linear structures present in the region. The methods enabled a semi-quantitative analysis, where the rosette diagrams show that the three variables (lineaments, drainage and linear representation of crest) studied in the research are preferably grouped in the NW-SE direction. The diagnosis also showed that the drainage network and the linear representation of tops in the area are complex and variable, presenting distinct densities and patterns controlled by lineaments and lithology. The use of remote sensing data coupled with geoprocessing techniques proved to be effective in the analysis and characterization of the study area since it was possible to obtain information about geological structures and modeling in a fast way.